Model-Model Pembelajaran di Era 4.0 dan Disrupsi dalam Implementasi - Muhammad Arifin; Muhammad Umar; Arif Hidayat Siregar (Departement of Mathematics Education, 2024)
Learning is basically a condition that makes learners to learn. Teachers as learning subjects are required to master various learning models in accordance with the material and student learning needs. The rapid development of the era marked by the industrial revolution that continues to advance, from the 1.0 era to the present which is recognized as being in the 4.0 era, certainly has an impact on the world of education. The demands of high quality education can be achieved, one of which is by transforming the learning model which slowly begins to shift following the direction of the times. The purpose of this study is to recommend relevant learning models to be implemented in the 4.0 era. The method used in this study is literature review with a descriptive qualitative approach, which takes data through documentation studies (literature). The result of this study is information that currently it can be said to be in the 4.0 era with several indicators in various industrial sectors ranging from FMCG, electronics, textiles, automotive, electronics, to financial and banking services. So, learning models that are considered relevant to be implemented today include; Blended Learning Flipped Classroom Project-Based Learning Problem-Based Learning Collaborative Learning Game-Based Learning